Preludes to pragmatism toward a reconstruction of philosophy - Kitcher, Philip, 1947- (New York ; Oxford : Oxford University Press, 2013)
Over the last two decades the distinguished philosopher Philip Kitcher has started to make a serious case for pragmatism as the source of a new life in contemporary philosophy. There are some, like Kitcher, who view today's analytic philosophy as mired in narrowly focused, technical disputes of little interest to the wider world. What is the future of philosophy, and what would it look like? These essays try to install the pragmatic spirit into contemporary philosophy, renewing James and Dewey for our own times.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Includes index.
Keywords: Pragmatism